Effect of Replacing Maize with Brewer’s Dried Grain in Broiler Finisher Diet - Ironkwe, M.O.; Bamgbose, A.M. (International Journal of Poultry Science, 2011)
The experiment was carried out using two hundred 4 weeks old broiler finisher birds to evaluate their response to diet with different levels of Brewers Dried Grain (BGD). The diet was made to replace maize with brewer’s dried grain at 0%, 25%, 50%, 75% and 100% to form treatment diets, 1, 2, 3, 4 and 5 respectively. The formulated rations were made in such a way that other ingredients apart from maize and brewer’s dried grain remained the same. The two hundred 4 weeks old broiler birds of Anak ® strains were allotted in a completely randomized Design into five treatment groups. Each treatment had 40 birds, which was replicated two times with 20 birds each. The experiment lasted for eight weeks with feed and water provided ad-libitum. Results showed significant differences in the birds growth performance, birds in T3 had the most superior (p<0.05) final live weight, daily weight gains and feed conversion ratio, followed by T2, T4 and T5. The least value was obtained from birds in T1. The daily feed intake showed a reverse trend, as birds consumption significantly (p<0.05) improves as the level of maize increased in the diet, with the highest (p<0.05) intake recorded for birds in T1 (100% maize, the least value from birds in T5 (100% brewer’s dried grains), the least cost per kg of feed was obtained from diet (T5), it decreased as the brewer’s dried grain increased in the diet. Cost per kg weight gain showed a similar trend and tended to favour birds fed higher levels of brewer’s dried grain. The use of brewer’s dried grain in broiler finisher diet should be encouraged as it gave promising results in terms of growth performance, better feed conversion and body weight gains.